Polystyrene/TiO2 composite electrospun fibers as fillers for poly(butylene succinate-co-adipate): Structure, morphology and properties - Neppalli, Ramesh; Causin, Valerio; Benetti, Edmondo Maria; Ray, Suprakas Sinha; Esposito, Antonella; Wanjale, Santosh; Birajdar, Mallinath S.; Saiter, Jean-Marc; Marigo, Antonio (European Polymer Journal, 2014)
In this work, composite polystyrene/titanium dioxide (PS/TiO2) electrospun fibers were used as a reinforcement for a poly(butylene succinate-co-adipate) (PBSA) matrix. The structure, morphology, mechanical properties and degradation behavior of such materials were investigated, finding that, as a function of their TiO2 content, the fibers exerted different effects. The main mechanism through which the fibers modified the structure and morphology of the polymer matrix is by altering its crystallization kinetics. The presence of TiO2 modified the roughness of the fibers and therefore affected the interfacial adhesion between the filler and the matrix. The modulus of PBSA was improved, even though the brittleness of the materials was increased by the presence of the fibers. Different amounts of TiO2 within the fibers allowed to tune the hydrolytic degradation rate of the composites. This paper shows the potential of using composite electrospun fibers as effective fillers for the preparation of polymer-based composites. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymers; Degradation; electrospinning; Morphology; Nanocomposites; Polycaprolactone